TAFSIR HERMENEUTIK DAN FENOMENOLOGI DALAM AL-QURAN - Zubairin, Ahmad (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Al-Quran is the holy book of humanist Muslims. The entire content of the verse leads to humanizing humans, not the other way around. However, this noble goal has not been fully realized, it is allegedly by some circles because the methodology in the interpretation of the Qur'an still uses celestial language which is difficult to reason and apply. The interpreters of the Qur'an are still "preoccupied" with textual interpretations, even though if they borrow the humanities methodology, the interpreters will find a humanist interpretation, which is compatible with modern human values. Hermeneutics and Phenomenology are part of a humanist scientific methodology. Hermeneutics works by exploring the meaning behind the text of the scriptures, while phenomenology is an empirical method based on human phenomena with their reality. Both methods have a philosophical essence in their application, so that applying both methodologies in the study of the Qur'an is basically an effort to explore the deepest meaning of the Qur'an, which can usually be found in the interpretation of literary styles.